One day at the bottom of the deep blue sea - Bernstrom, Daniel (Hippo Park, an imprint of Astra Books for Young Readers, a division of Astra Publishing House, 2025)
"A clever little girl 'with a net for catching pearls' meets a shark who wants nothing more than to eat her for dinner."--